(untitled) (International Seven Journal of Health Research, 2024)
Introduction: Obesity is linked to some types of cancer, such as those of the gastrointestinal tract (esophageal, liver, gallbladder, stomach, pancreas and colorectal cancer), ovary and thyroid. Objective: to describe the association of the main factors related to the relationship between obesity and the pathophysiology of gastrointestinal cancer, nutrition and the intestinal microbiota. Material and Methods: This article is a systematic review, based on the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) methodology. Results and Discussion: Obesity increases the concentrations of insulin, IGF1 and IGF2, which in turn reduce apoptosis and stimulate cell growth. With increased adiposity, there is also an increased production of pro-inflammatory cytokines such as interleukin-6 (IL-6) and interleukin-8 (IL-8), tumor necrosis factor (TNF) and C-reactive protein. Conclusion: Given the evidence presented in this study, it is observed that expanding adipose tissue may have a clinically relevant contribution to the development of gastric cancer. A greater understanding of the mechanisms of obesity-induced carcinogenesis is needed to develop methods to prevent or treat gastric cancer. A greater understanding of the molecular mechanisms present in obesity may lead to the identification of new therapeutic targets.